The effect of ethnic diversity on income: An empirical investigation using survey data from a post-conflict environment - Adnan Efendic; Geoff Pugh (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
This empirical study is based on nationally representative cross-sectional survey data gathered to investigate the effect of ethnic diversity on personal and family incomes in Bosnia and Herzegovina (BiH), a post-conflict society. The 1992-1995 conflict was harmful for ethnic diversity. Yet, two decades later, where it still exists, ethnic diversity gives rise to positive economic consequences. After controlling for other influences, the authors find lower probabilities of respondents in ethnically diverse neighbourhoods being in the lowest income categories but higher probabilities of being in medium and higher income categories. The largest effects are the reduced probabilities of respondents reporting no income, and are thus particularly relevant to poverty reduction. At the limit, their estimates imply an income gap of more than 20 per cent between a counter-factual completely heterogenous environment and a counter-factual completely homogenous environment. Policy makers in this post-conflict country, and in similar environments elsewhere, should take into consideration the economic costs of policies supporting ethnic homogeneity over diversity.
Keywords: D00; D10; D31; 330; ethnic diversity; income; poverty reduction; Bosnia and Herzegovina; post-conflict societies